Bone marrow trephine combined with immunohistochemistry is superior to bone marrow aspirate in follow-up of myeloma patients. Issue 2 (25th May 2007) - Joshi, R; Horncastle, D; Elderfield, K; Lampert, I; Rahemtulla, A; Naresh, K N
Abstract : Aims: Multiple myeloma (MM) guidelines in the UK do not advocate performing bone marrow trephine biopsy (BMTB) during follow-up. In a recent study, it was found that the plasma cell per cent (PC%) in BMTB performed at the time of autologous stem cell transplant strongly correlated with survival. The current study addresses whether BMTB is superior to bone marrow aspiration (BMA) in documenting presence of disease and its volume at follow-up. Methods: The study involved 106 samples. A conventional 500-cell differential count was performed on the BMAs to document the PC%. The PC% on BMTBs had been estimated on CD138 immunostain. Furthermore, BMTBs had also been immunostained for CD56, cyclin D1 and light chains. Results: The mean (2SEM) PC% values in BMAs and BMTBs were 13.1 (2.6)% and 31.8 (5.8)% respectively. Based on BMA, BMTB and serum/urine paraprotein or light chain estimation, on 92 occasions (89%) there was detectable disease. The positive predictive value of both BMA and BMTB was 100%, and the negative predictive values for BMTB and BMA were 57% and 22% respectively. Among 98 secretory MM cases, the BMTB-PC% showed significant correlation with paraprotein levels, whereas BMA-PC% did not. Conclusions: It is strongly recommended that BMTB is performed and adequately investigated with immunohistochemistry during follow-up of MM.